2019
DOI: 10.1155/2019/9194560
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization, and Safety Evaluation of Human Skin-Derived Precursors from an Adherent Monolayer Culture System

Abstract: Background. Skin-derived precursors (SKPs) are promising candidates for regenerative medicine. Several studies have transcultured human SKPs (termed tSKPs) from fibroblasts (FBs) expanded in monolayer culture. Herein, we optimized the procedure by treating flasks with poly-2-hydroxyethyl methacrylate (poly-HEMA). Methods. tSKPs generated from our adherent monolayer culture system were investigated for protein expression and differentiation capacity. The aggregated cells and the proliferative cells within tSKP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Rabbit skin fibroblasts were isolated according to the previously described methods [28]. The skin was isolated from female WT and Xist P1 −/rabbits and cut into 0.5-mm 3 pieces.…”
Section: Cell Line Isolationmentioning
confidence: 99%
“…Rabbit skin fibroblasts were isolated according to the previously described methods [28]. The skin was isolated from female WT and Xist P1 −/rabbits and cut into 0.5-mm 3 pieces.…”
Section: Cell Line Isolationmentioning
confidence: 99%
“…The protocol for isolating tSKPs has been described previously in our study (6). For directing tSKPs into tFBs, spheres were collected, resuspended in dulbecco's modified eagle medium (DMEM) containing 10% fetal bovine serum, and then seeded into cell culture dishes.…”
Section: Cell Preparationmentioning
confidence: 99%
“…Conventionally, SKPs are cultured as floating spheres in suspending serum-free medium with required growth factors (3); however, many studies have reported that isolating human SKPs by this protocol has many limitations such as relatively low yield (4), slow growth rate (3), and heterogeneous spheres (5). Therefore, it is unsurprising that several studies have demonstrated a new technique to transculture human SKPs from adherent monolayer culture system (henceforth termed tSKPs), and these tSKPs are similar to traditional SKPs in morphology and function (6)(7)(8). Developments in tSKPs research have indicated their potential application in regenerative medicine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). Current techniques for cell isolation and culture in vitro make it possible to obtain potential cells, such as dermal papilla cells (DPCs), skin-derived precursors (SKPs), and hair follicle stem cells (HFSCs) [ [21] , [22] , [23] ]. These cells can be enmeshed in a biomaterial matrix, which mimics the chemical structure of HF extracellular matrix (ECM) and provides specific effects in regulating cell behaviors, such as cell survival, proliferation, and differentiation [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%